Particle Size Dynamics: Toward a Better Understanding of Electronic Cigarette Aerosol Interactions With the Respiratory System - Sosnowski, Tomasz R.; Odziomek, Marcin (Frontiers in Physiology, 2018)
The knowledge of possible acute and long-term health effects of aerosols inhaled from electronic cigarettes (ECs) is still limited partially due to incomplete awareness of physical phenomena related to EC-aerosol dynamics. This short review discusses the basic processes of aerosol transformation (dynamics) upon inhalation, indicating also the need for the accurate determination of the size of droplets in the inhaled EC-mist. The significance of differences in the aerosol particle size distribution for the prediction of regional deposition of inhaled mist in the respiratory system is highlighted as a decisive factor in the interactions of inhaled EC-aerosols with the organism.